Creative Art Work Atisundara | Tabuh Kreasi Atisundara - Kadek Krisna Dwipa Diartama; Ni Made Arshiniwati; Ni Ketut Suryatini (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
In the process of forming this work, we get a touch of idea when we see a bird of paradise that is very beautiful and beautiful to look at, the beauty of its feathers and the combination of colors that produce a very beautiful harmonization when viewed. Then from there I got the idea to create a work of art based on a bird of paradise, and after looking for references to books and I got one word for the title of the work I will create, namely